Application of mesoporous silica nanoparticles as drug delivery carriers for chemotherapeutic agents. Issue 8 (August 2020) - Alyassin, Yasmine; Sayed, Elshaimaa G.; Mehta, Prina; Ruparelia, Ketan; Arshad, Muhammad S.; Rasekh, Manoochehr; Shepherd, Jennifer; Kucuk, Israfil; Wilson, Philippe B.; Singh, Neenu; Chang, Ming-Wei; Fatouros, Dimitrios G.; et al.
Highlights: Structural and geometrical features of mesoporous silica can benefit drug delivery. Coupled with therapeutic agents, targeting for a host of cancers is possible. Several shortcomings of existing therapies are shown to be overcome. Abstract : Recently, remarkable efforts have focused on research towards enhancing and delivering efficacious and advanced therapeutic agents. Even though this involves significant challenges, innovative techniques and materials have been explored to overcome these. The advantageous properties of mesoporous silica nanoparticles (MSNs), such as unique morphologies and geometries, makes then favorable for use for various drug delivery targeting purposes, particularly in cancer therapy. As we discuss here, MSNs have been utilized over the past few decades to improve the efficiency of anticancer drugs by enhancing their solubility to render them suitable for application, reducing adverse effects, and improving their anticancer cytotoxic efficiency.